USA: Ophthalmologic Evaluation and Management of Acute Stevens-Johnson Syndrome - Gregory, Darren G. (Frontiers in Medicine, 2021)
Abstract: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) can cause significant damage to the ocular surface and eyelids. The intense inflammation during the acute phase may lead to scarring sequelae and vision loss. Treatment of the chronic manifestations is challenging and only partially effective in many cases. Ophthalmologic evaluation and management during the acute phase is crucial in avoiding these problems. The current evaluation and management of patients with SJS and TEN in the USA is described, with an emphasis on amniotic membrane transplantation as an effective means of limiting the acute phase damage.